Occupational and social hazards among domestic solid waste collectors: a cross sectional study - Patil, Tanvi; Raje, Swati S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Domestic solid waste collectors play important role in maintain hygiene of a community, especially in developing countries. Yet not many efforts are done to identify their health needs. The main objective of this study is to identify the morbidity pattern and social problems of solid waste collectors in urban Maharashtra. Methods: It was a cross sectional study. Study population consisted of domestic solid waste collectors who are registered under municipal corporation. Sampling was purposive. All the domestic solid waste collectors who came for specially arranged health check-up were included in the sample. Social and demographic information along with clinical history was collected using a structured questionnaire. General physical exam, eye checkup, skin examination and lab investigations were done in a specially organized camp, after obtaining prior consent of the participants. Data was analyzed using SPSS 19 software. Results: More than 90% of 98 solid waste collectors, who participated in the study had frequent cough, fever and diarrhea. Over 85% had back or/and leg pain. More than half of the study population had dryness of skin and 47% of them complained of itching. 15 solid waste collectors were discriminated in marriages. Conclusions: High prevalence of common frequent symptoms such as fever, cough and diarrhea can be controlled by conducting regular health checkups for this community. The need is to reach them rather than waiting for them to come to health facility. Sensitization of community towards importance of work done by the solid waste collectors is also required.